Hellenistic bell-shaped situlae with ivy leaves - Martina Blečić Kavur (Arheološki Vestnik, 2022)
Situla art, as a specific visual and semantic synthesis, connected numerous culturally different societies of the prehistoric and historic Iron Age of Europe. Situlae themselves, which gave the name to this art phenomenon, were not only carriers of artistic expression and symbolic narrative, but also reflected a cognitive maturity and sublimation of society as an accepted emblem of the way individual aristocracies represented their status. The area of the northern Adriatic boasts examples of the Early Iron Age situla art and the later, ‘Hellenistic’ situlae. The starting point of the present research are the fragments of Hellenistic bell-shaped situlae decorated with ivy leaves from Rijeka, which are analyzed typologically, as well as stylistically and iconographically in comparison with all the hitherto known situlae of this type. The article brings an updated list of bell-shaped situlae, presents arguments for their more precise chronological position, their typological and technological division into two major groups with variants and the related different toreutic centres of production. The distribution of Hellenistic bell-shaped situlae with ivy leaves shows that the eastern Adriatic coast and its hinterland were a place of contact between Macedonian and Etruscan luxury toreutic products.